2013
DOI: 10.1111/echo.12216
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Speckle Tracking Echocardiography for Early Detection of Myocardial Damage in Young Patients with Fabry Disease

Abstract: Fabry disease (FD) is characterized by left ventricular hypertrophy (LVH). Conventional echocardiography is not sensitive enough to perform the preclinical diagnosis To assess whether longitudinal myocardial strain of the left ventricle (LV), using speckle tracking, is useful to detect early myocardial involvement in FD. Forty-four patients with FD who were diagnosed with genetic testing were prospectively included and were compared to a sex-matched control group. They were divided into three groups: 22 with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 24 publications
3
30
0
1
Order By: Relevance
“…Imbalzano et al found that the patients with hypertension but no LVH only showed significantly lower GLS compared with the controls . Saccheri et al also observed that the patients with Fabry disease and LVN had significantly lower longitudinal strain in only two segments . In a 3DSTE study, Ternacle et al even found no significant differences in GLS, GCS, GAS, and GRS between the athletes with LVN and the controls .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Imbalzano et al found that the patients with hypertension but no LVH only showed significantly lower GLS compared with the controls . Saccheri et al also observed that the patients with Fabry disease and LVN had significantly lower longitudinal strain in only two segments . In a 3DSTE study, Ternacle et al even found no significant differences in GLS, GCS, GAS, and GRS between the athletes with LVN and the controls .…”
Section: Discussionmentioning
confidence: 97%
“…16 Saccheri et al also observed that the patients with Fabry disease and LVN had significantly lower longitudinal strain in only two segments. 17 In a 3DSTE study, Ternacle et al even found no significant differences in GLS, GCS, GAS, and GRS between the athletes with LVN and the controls. 18 Similarly, in our study, GLS was the only significantly lower strain value in the T2DM patients with LVN than in the controls.…”
Section: Dysfunction In T2dmmentioning
confidence: 92%
“…[8][9][10][11][12][13] An early reduction of global longitudinal strain (GLS) has been clearly demonstrated in this clinical setting. [8][9][10] GLS has also been used to differentiate AFD from other types of LVH. 10 Recent advancements in speckle tracking technology make now available the analysis of layer-specific myocardial deformation, allowing focused longitudinal strain measurements at subendocardial and subepicardial level (LSsubendo and LSsubepi, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Fabry disease is rare and usually multisystemic, but occasionally is expressed clinically as a predominantly cardiac phenotype mimicking HCM. The LVH in patients with Fabry disease is usually symmetric, not asymmetric as in HCM . The asymmetric septal hypertrophy observed in about 5% of the cases is similar to sarcomeric cardiomyopathies.…”
Section: Discussionmentioning
confidence: 91%